Pore-scale modeling of wettability effects on CO2–brine displacement during geological storage - Basirat, Farzad; Yang, Zhibing; Niemi, Auli (Advances in water resources, 2017)
•Wetting condition does not appear to effect the CO2 breakthrough time and saturation.•Decreasing contact angle rises trapped wetting phase saturation and interfacial area.•CO2 relative permeability can be significantly lower in strongly water-wet rocks. Wetting properties of reservoir rocks and caprocks can vary significantly, and they strongly influence geological storage of carbon dioxide in deep saline aquifers, during which CO2 is supposed to displace the resident brine and to become permanently trapped. Fundamental understanding of the effect of wettability on CO2–brine displacement is thus important for improving storage efficiency and security. In this study, we investigate the influence of wetting properties on two-phase flow of CO2 and brine at the pore scale. A numerical model based on the phase field method is implemented to simulate the two-phase flow of CO2–brine in a realistic pore geometry. Our focus is to study the pore-scale fluid-fluid displacement mechanisms under different wetting conditions and to quantify the effect of wettability on macroscopic parameters such as residual brine saturation, capillary pressure, relative permeability, and specific interfacial area. Our simulation results confirm that both the trapped wetting phase saturation and the normalized interfacial area increase with decreasing contact angle. However, the wetting condition does not appear to influence the CO2 breakthrough time and saturation. We also show that the macroscopic capillary pressures based on the pressure difference between inlet and outlet can differ significantly from the phase averaging capillary pressures for all contact angles when the capillary number is high (log Ca > −5). This indicates that the inlet–outlet pressure difference may not be a good measure of the continuum-scale capillary pressure. In addition, the results show that the relative permeability of CO2 can be significantly lower in strongly water-wet conditions than in the intermediate-wet conditions.